PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA KANTOR DPRD KEPULAUAN MERANTI - Wan Sasriani; Indra Prasetyo; Woro Utari (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
The purpose of this study was to identify and analyze competency descriptions, work environment, employee performance and employee job satisfaction in the Meranti Islands Regency DPRD Office. To find out and analyze the effect of competence and work environment on employee performance through job satisfaction. This type of research is explanatory research using a quantitative approach. The population in this study were all employees in the Meranti Islands Regency DPRD Office, totaling 37 people. As for the sample in this study were 37 people. The sampling technique uses census sampling. Data analysis was performed using Partial Least Square (PLS). The results of the study can be concluded that performance, satisfaction, competence, work environment in the Secretariat Office of the DPRD Meranti Islands Regency are in the high category, Competence has a significant effect on Performance, Work environment has no significant effect on Performance, Job satisfaction has a significant effect on Performance, Competence has a significant effect on Satisfaction work, work environment has no significant effect on job satisfaction, competence has a significant effect on performance through job satisfaction, work environment has no significant effect on performance through job satisfaction.